Profil Resiliensi Guru Matematika SMP di Masa Pandemi Covid-19 Ditinjau dari Kompetensi Pedagogik - Chrisma Wuri Haryaningrum; Ginanjar Setyo Nugroho (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This is a descriptive qualitative research. Three mathematics teachers from SMP N 3 Gamping were the subjects of this investigation. Data collection techniques used are interviews and documentation. Data reduction, data presentation and drawing conclusions are all approaches used in data analysis. The validity of the data used are source triangulation and data triangulation.The results showed that in the aspect of student understanding and evaluation of learning outcomes, research subjects were able to control their emotions, consider decisions taken, have confidence, have obstacles experienced, have empathy, have self-efficacy that can help solve problems, have a willingness to continue learning to improve abilities. In the aspect of designing and implementing learning. There are still teachers who feel burdened, there are teachers who do not have self-confidence. The research subject will consider the platform used in online learning that is adapted to the student's condition, has obstacles, has confidence that he can solve the problems at hand, has the willingness to continue learning to improve his abilities. In the aspect of using technology, there are teachers who feel burdened, there are teachers who experience obstacles in using technology, research subjects consider the technology used, have the confidence to be able to master technology, can feel the condition of students who have insufficient cellphone capacity, have confidence that they can overcome problems that arise. faced, have the willingness to continue to learn to improve skills in technology.